THE EFFECTIVENESS OF PROJECT-BASED LEARNING THROUGH MAKING ENGLISH VLOGS TO IMPROVE STUDENTS SPEAKING ABILITY - Ance - Jusmaya (INOVISH JOURNAL, 2022)
This research is focused on developing students' speaking ability through Project Based Learning method by making vlogs about Pariaman Tourism. This is based on the findings of previous research which showed that the majority of students at the University of West Sumatra still have low English skills. The design of this research is a quasi-experimental research that wants to know the effect of Project Based Learning by making vlogs on the speaking ability of students at the University of West Sumatra. To determine the students' speaking ability, this study used a speaking test, through three pre-test and post-test. The pre-test was used to see the speaking ability before undergoing treatment and the posttest was used to see the difference in students' speaking scores after being given treatment. The research subjects were students from the Management Department at the University of West Sumatra who took English class 2. The data found showed that Project Based Learning using vlogs had a significant effect on students' speaking skills. This conclusion can be seen based on the analysis that has been carried out where t table t is observed. t observed = 3.80 and t table 2.30 with a standard significance of 0.05. So, it can be concluded that students' speaking skills can be improved by using the Project Based Learning method in making vlogs.